2000
DOI: 10.1901/jaba.2000.33-347
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Reinforcer Choice Measured in Single‐operant and Concurrent‐schedule Procedures

Abstract: The effects of choice and no choice of reinforcer on the response rates of 3 children with autism were compared across single-operant and concurrent-schedule procedures. No consistent differences in responding between choice and no-choice components emerged during single-operant phases. During the concurrent-schedule phases, however, all participants had substantially higher rates of responding to the button that led to a choice among reinforcers than to the button that did not lead to choice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
23
0
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 6 publications
1
23
0
1
Order By: Relevance
“…The third participant's responding was not affected differentially by choice and no‐choice conditions until they were compared in a concurrent‐operants format. These results provide additional support that choice making may enhance the efficacy of reinforcement‐based interventions (e.g., Brigham & Sherman, 1973; Fisher et al, 1997; Tiger et al, 2006) and are also similar to those of Geckeler et al (2000), who demonstrated that single‐operant arrangements using FR schedules were insensitive to the added value of choice. The combined results of Geckeler et al and the current study support the assertion that Lerman et al (1997) and Smith et al (1995) may have failed to identify differential reinforcement effects associated with choice conditions due to the ceiling effects imposed by single‐operant arrangements.…”
Section: Resultssupporting
confidence: 62%
See 1 more Smart Citation
“…The third participant's responding was not affected differentially by choice and no‐choice conditions until they were compared in a concurrent‐operants format. These results provide additional support that choice making may enhance the efficacy of reinforcement‐based interventions (e.g., Brigham & Sherman, 1973; Fisher et al, 1997; Tiger et al, 2006) and are also similar to those of Geckeler et al (2000), who demonstrated that single‐operant arrangements using FR schedules were insensitive to the added value of choice. The combined results of Geckeler et al and the current study support the assertion that Lerman et al (1997) and Smith et al (1995) may have failed to identify differential reinforcement effects associated with choice conditions due to the ceiling effects imposed by single‐operant arrangements.…”
Section: Resultssupporting
confidence: 62%
“…These divergent results may be partially explained by the differing assessment formats. That is, concurrent‐operants assessments are differentially sensitive to reinforcer strength in part due to the absence of ceiling effects that may occur in single‐operant assessments (Geckeler, Libby, Graff, & Ahearn, 2000; Roscoe, Iwata, & Kahng, 1999).…”
mentioning
confidence: 99%
“…Often, choice is more preferred and is a relatively more potent reinforcer than no choice across a variety of species and populations (Catania & Sagvolden, 1980;Cerutti & Catania, 1997;Fenerty & Tiger, 2010;Geckeler, Libby, Graff, & Ahearn, 2000;Schmidt et al, 2009;Sran & Borrero, 2010;Thompson, Fisher, & Contrucci, 1998;Tiger et al, 2006;Tiger, Toussaint, & Roath, 2010;Voss & Homzie, 1970). Several studies have shown that not only is choice more preferred or a more potent reinforcer but also the preference for choice is relatively strong and sometimes resistant to change (e.g., Thompson et al, 1998;Tiger et al, 2006Tiger et al, , 2010.…”
mentioning
confidence: 99%
“…Areas of choice may include engagement or nonengagement in activities, choice between tasks or activities, material use, and partners (Shevin & Klein, 1984). Additionally, choice making among reinforcers has been shown to increase response rates (Geckeler, Libby, Graff, & Ahearn, 2000;Graff, & Libby, 1999 Martella, Marchand-Martella, & Ebey, 2000) and decrease problem behaviors (Dyer, Dunlap, & Winterling, 1990;Graff, Libby, & Green, 1998).…”
mentioning
confidence: 99%